Pelvic Trauma: Anatomy and Interventions - Leslie, Jacob F.; Smirniotopoulos, John B. (Seminars in Interventional Radiology, 2025)
Trauma, particularly pelvic trauma, is a leading cause of morbidity and mortality in the United States, with hemorrhage being the primary cause of death in these trauma patients. In particular, pelvic fractures often result in substantial vascular injuries, requiring rapid diagnosis, and intervention to prevent fatal outcomes. Multiphase computed tomography angiography (CTA) has emerged as the gold standard for assessing pelvic trauma, facilitating early identification of vascular injuries and active hemorrhage. Interventional radiology (IR) plays a key role in managing these injuries through angiography and embolization, effectively stabilizing hemodynamics and preventing long-term complications such as necrosis or claudication. The complex vascular anatomy of the pelvis, including variants like the corona mortis and aberrant obturator arteries, necessitates careful planning during angiography. Techniques such as nonselective embolization, selective embolization with temporary embolic, and coil embolization are critical in achieving hemostasis. While effective, these procedures carry risks, including rebleeding and complications such as neuropathy and gluteal necrosis. Early activation of the angiography suite and multiphase CTA are essential to improving patient outcomes. This review outlines the anatomy, evaluation, and management strategies for pelvic trauma, emphasizing the importance of rapid intervention and the integral role of IR in controlling hemorrhage and ensuring patient survival.
Keywords: pelvic trauma; arterial anatomy; angiography; embolization; interventional radiology